2022
DOI: 10.1186/s12876-022-02248-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and fecal zonulin are not altered by a high green leafy vegetable dietary intervention: secondary analysis of a randomized control crossover trial

Abstract: Background Zonulin is observed in animal models to regulate intestinal permeability and influenced by dietary intake, gut microbiota, and inflammation. We conducted a secondary analysis of a randomized controlled crossover trial (NCT03582306) in individuals with a BMI greater than 30 kg/m2 and high habitual red meat intake and low habitual green leafy vegetable (GLV) intake. Methods Participants were provided with frozen GLV during the first or las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…This issue may not be relevant if these ELISA kits correlate strongly with functional gut permeability as assessed via established tests [ 13 ]. At present, this is the best method for measuring zonulin levels in human samples and is widely used for measuring intestinal permeability [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This issue may not be relevant if these ELISA kits correlate strongly with functional gut permeability as assessed via established tests [ 13 ]. At present, this is the best method for measuring zonulin levels in human samples and is widely used for measuring intestinal permeability [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors such as diet may have an important role in regulating intestinal integrity [ 61 , 62 ]. A study that targeted intestinal permeability by treating mice with butyrate found that a reduction in the severity of the observed arthritis was due to the improvement of intestinal permeability and was associated with a reduction in serum zonulin concentrations [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is considered one of the main factors that guarantee the good function of the intestinal barrier due to its effects on epithelial tightness. Increased concentrations of zonulin in blood or feces have been correlated with the important alteration of intestinal permeability in the case of diabetes, IBS, or IBD [ 52 ].…”
Section: Intestinal Permeability-definition and Methods Of Evaluationmentioning
confidence: 99%